2013
DOI: 10.1002/14651858.cd004807.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Consumer-providers of care for adult clients of statutory mental health services

Abstract: Involving consumer-providers in mental health teams results in psychosocial, mental health symptom and service use outcomes for clients that were no better or worse than those achieved by professionals employed in similar roles, particularly for case management services.There is low quality evidence that involving consumer-providers in mental health teams results in a small reduction in clients' use of crisis or emergency services. The nature of the consumer-providers' involvement differs compared to professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
249
1
18

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(274 citation statements)
references
References 146 publications
6
249
1
18
Order By: Relevance
“…Furthermore, a recent Cochrane Review has indicated that the equivocal nature of findings in trials of peer worker intervention to date is at least in part due to poor definition of the intervention and associated mechanisms of change. 16 Coherent future evaluation that usefully informs service provision in England might therefore be prioritised as follows:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recent Cochrane Review has indicated that the equivocal nature of findings in trials of peer worker intervention to date is at least in part due to poor definition of the intervention and associated mechanisms of change. 16 Coherent future evaluation that usefully informs service provision in England might therefore be prioritised as follows:…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the overall picture demonstrating the effectiveness of peer worker interventions remains less than convincing. 16 Medical Research Council guidance for the evaluation of complex interventions 21 suggests that sufficient theoretical, modelling and piloting work needs to be done around complex, organisational or service-level interventions before properly informed decisions can be made about what to evaluate and how. The introduction of peer workers into existing teams alongside other mental health professionals within the NHS, or establishing innovative peer-led services in partnership with or outside of statutory mental health service provision, constitute complex approaches to mental health care.…”
Section: Recommendations For Researchmentioning
confidence: 99%
“…Peer support can be provided informally through mutual support of friends and acquaintances sharing similar experiences; through the provision of userrun services; or through formal peer support. Now, increasingly, mental health service providers are attempting to harness this naturally occurring companionship to provide more formal peer support either alongside or in place of mainstream or 'professional' mental health services (Repper 2013), often with impressive results (Pitt et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Among participants that worked in close proximity with peer specialists, between 52 and 65 % of their consumers were referred for peer support services. The referral rate on the team with a peer specialist was much higher at 97 % [5].…”
Section: Administrative Factorsmentioning
confidence: 92%
“…Peer supported services have been associated with positive consumer outcomes including reduced symptoms, increased functioning in activities of daily living, enhanced sense of empowerment, and decreased service utilization [2,3]. While other studies have found moderate or little impact of peer support services on consumer outcomes [4,5]. However, the promise of peer provided services supported by the recovery community and research have propelled the implementation of peer support services forward.…”
Section: Introductionmentioning
confidence: 99%